Community Perception of the Position of Dayak Kanayatn Traditional Marriages Compared to Catholic Church Marriages in Menjalin District, Landak Regency - Magdalena, Magdalena; Kristianus, Kristianus; Lodo, Mikael Dou (STKIP Singkawang, 2024)
This research was motivated by the rise of traditional marriages carried out by the Indigenous Peoples of the Menjalin Subdistrict, Landak Regency. From the author's search, not many of them do marriage in marriage and marriage in the State. This research aimed to determine perceptions of tradition and Catholic marriages. This research was conducted using the ethnographic method in the period of June-December 2023. The subjects of this research were Dayak Traditional leaders and Catholic religious leaders. Data was collected by observation and in-depth interviews. The data analysis technique involved coding each question and interpreting it. The findings of this study indicated that the public's perception of traditional marriage was legal. The Kanayatn Dayak Indigenous people see that customary marriage is more important than church and state marriage. This perception was influenced by a strong belief in their culture, where they felt more guilty towards the spirits of their ancestors if they did not carry out marriage customs compared to state marriages. Another thing was lazy administration with the church and the government.